Conversion from NFA with ε to DFANondeterministic finite automata(NFA) is a finite automata where for some cases when a specific input is given to the current state, the machine goes to multiple states or more than 1 states. It can contain ε move. It can be represented as M = { Q, ∑, δ, q0, F}. Where NFA with ∈ move: If any FA contains ε transaction or move, the finite automata is called NFA with ∈ move. εclosure: εclosure for a given state A means a set of states which can be reached from the state A with only ε(null) move including the state A itself. Steps for converting NFA with ε to DFA:Step 1: We will take the εclosure for the starting state of NFA as a starting state of DFA. Step 2: Find the states for each input symbol that can be traversed from the present. That means the union of transition value and their closures for each state of NFA present in the current state of DFA. Step 3: If we found a new state, take it as current state and repeat step 2. Step 4: Repeat Step 2 and Step 3 until there is no new state present in the transition table of DFA. Step 5: Mark the states of DFA as a final state which contains the final state of NFA. Example 1:Convert the NFA with ε into its equivalent DFA. Solution: Let us obtain εclosure of each state. Now, let εclosure {q0} = {q0, q1, q2} be state A. Hence δ'(A, 0) = εclosure {δ((q0, q1, q2), 0) } = εclosure {δ(q0, 0) ∪ δ(q1, 0) ∪ δ(q2, 0) } = εclosure {q3} = {q3} call it as state B. δ'(A, 1) = εclosure {δ((q0, q1, q2), 1) } = εclosure {δ((q0, 1) ∪ δ(q1, 1) ∪ δ(q2, 1) } = εclosure {q3} = {q3} = B. The partial DFA will be Now, δ'(B, 0) = εclosure {δ(q3, 0) } = ϕ δ'(B, 1) = εclosure {δ(q3, 1) } = εclosure {q4} = {q4} i.e. state C For state C: The DFA will be, Example 2:Convert the given NFA into its equivalent DFA. Solution: Let us obtain the εclosure of each state. Now we will obtain δ' transition. Let εclosure(q0) = {q0, q1, q2} call it as state A. δ'(A, 0) = εclosure{δ((q0, q1, q2), 0)} = εclosure{δ(q0, 0) ∪ δ(q1, 0) ∪ δ(q2, 0)} = εclosure{q0} = {q0, q1, q2} δ'(A, 1) = εclosure{δ((q0, q1, q2), 1)} = εclosure{δ(q0, 1) ∪ δ(q1, 1) ∪ δ(q2, 1)} = εclosure{q1} = {q1, q2} call it as state B δ'(A, 2) = εclosure{δ((q0, q1, q2), 2)} = εclosure{δ(q0, 2) ∪ δ(q1, 2) ∪ δ(q2, 2)} = εclosure{q2} = {q2} call it state C Thus we have obtained The partial DFA will be: Now we will find the transitions on states B and C for each input. Hence δ'(B, 0) = εclosure{δ((q1, q2), 0)} = εclosure{δ(q1, 0) ∪ δ(q2, 0)} = εclosure{ϕ} = ϕ δ'(B, 1) = εclosure{δ((q1, q2), 1)} = εclosure{δ(q1, 1) ∪ δ(q2, 1)} = εclosure{q1} = {q1, q2} i.e. state B itself δ'(B, 2) = εclosure{δ((q1, q2), 2)} = εclosure{δ(q1, 2) ∪ δ(q2, 2)} = εclosure{q2} = {q2} i.e. state C itself Thus we have obtained The partial transition diagram will be Now we will obtain transitions for C: δ'(C, 0) = εclosure{δ(q2, 0)} = εclosure{ϕ} = ϕ δ'(C, 1) = εclosure{δ(q2, 1)} = εclosure{ϕ} = ϕ δ'(C, 2) = εclosure{δ(q2, 2)} = {q2} Hence the DFA is As A = {q0, q1, q2} in which final state q2 lies hence A is final state. B = {q1, q2} in which the state q2 lies hence B is also final state. C = {q2}, the state q2 lies hence C is also a final state.
Next TopicMinimization of DFA
